Analytical Study on Piezoelectric Effects on Exciton Dissociation (Communications in Computational Physics, 2018)
We analytically and numerically compute the Onsager dissociation rate (excitondissociation) on an interface induced by a piezoelectric potential in an inorganic-organichybrid p-n junction system (ZnO + (poly(p-phenylene vinylene)); PPV).When a positive piezoelectric potential is created at the interface region owing to thedeformation of the system, free electrons accumulate at the interface. Hence, screeningeffects are observed. It is assumed that the electron layer formed at the interface thenattracts free holes from the p-type PPV region, which leads to exciton formation, possiblyvia the Langevin recombination process. The increased exciton density can thencontribute to the Onsager dissociation rate, which is maximum around the interface.This paper focuses on the role of piezoelectric effects in promoting exciton formationat the interface and its relation with the exciton dissociation rate.